Sosialisasi Penggunaan Tata Bahasa Yang Baik Dalam Meningkatkan Pemasaran Produk Ekonomi Di Kelurahan Padang Masiang Kecamatan Barus Kabupaten Tapanuli Tengah - Heriyawan Hutagalung; Jeniusman Ahmad Hutagalung; Fauziah Nur Simamora; Mhd. Safwan Koto (COVIT (Community Service of Health), 2023)
The objectives of implementing the community partnership program (PKM) service are (1) understanding PKM in the Padang Masiang Village community, (2) understanding in socialization in the Padang Masiang Village community, (3) understanding the importance of using good grammar in improving the marketing of economic products in the Padang Masiang sub-district. The method of implementing activities using good grammar in increasing the marketing of economic products includes several stages, namely: (1) Preliminary Stage, (2) Socialization and Audience Stage, (3) Final Evaluation Stage. The result of this activity is that the community understands how important it is to use good language in increasing the marketing of economic products in the Padang Masiang sub-district. The PKM community service partner is Padang Masiang Village, Barus District, Central Tapanuli Regency. This program is carried out as an effort to increase public knowledge in increasing product marketing and improving the economy of local residents. Keywords : Marketing, Product, Grammar